Exploring Trends and Innovations in Industrial Psychology Practice at a manufacturing company in Bekasi - Afnan, Nur Muhammad; Wicaksana , Muhammad Yudha Satria; Ayubi , Muhammad Firdaus Al; Herawan, Muhammad; Marbun, Adrian Valerius (Lentera Ilmu Nusantara, 2025)
This study explores trends and innovations in industrial psychology practices in manufacturing companies in Bekasi during the period 2012-2015. The main objective of this study is to identify how technological developments and positive psychology approaches affect human resource management in the context of a dynamic and stressful manufacturing industry. A systematic literature review method was used to analyze various relevant scientific and practical sources, focusing on aspects of employee selection and recruitment, competency development through digital training, stress management, and transformational leadership. The results of the study indicate that the application of technology such as computer-based recruitment management systems and Artificial Intelligence, e-learning-based training, and well-being programs that integrate mindfulness and mental health applications significantly improve workforce effectiveness and well-being. This study concludes that the integration of technological innovation and humanistic approaches in industrial psychology is a strategic key to improving employee productivity and well-being in Bekasi manufacturing companies. The practical and academic implications of these findings are expected to be the basis for sustainable human resource development in facing future industrial challenges.